CYBER CRIMES ISSUES AND CHALLENGES - Dr. Dhara R. Thakar (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2020)
This is highly needed to maintain the prosperity and peace of a country. A country where people live in harmony stands a far better prospect of development and growth as compared to one where people lack unity. As such, the govt must take initiatives to promote and invoke the feeling of oneness among citizens. When it comes to national integration, it is a psychological process and can knit society where all are loyal to their country. This is very crucial for the all-round development of the country, and at very must its existence depends on it. Now, there are various climates in India. Even there is a difference in beliefs and faiths, crops, and food habits. When it comes to dresses, even their dresses are different along with the conventions and customs which are varied and vast Here, people pursue a range of religions and sects. Also, there is uneven in the lands. You can see the northern region seems very fertile while in southern there are plateaus, barren lands, and desserts, along with hills and mountain ranges.